Finite element analysis of stresses and creep in turbine casings - Parkes, D.A.C. (1973)
The finite element method has been used to calculate the stresses and creep deformations of flanged turbine casing models subjected to internal pressure and bolting forces. The finite element results have been compared with results from photoelastic and lead model turbine casings.